Resin film

The resin film with a surface layer containing 30% cellulose particles achieves low peel strength and high biodegradability by using cellulose structures with specific molecular weights and porous structures, addressing the challenge of high peel strength in biodegradable resin films.

JP2024178895APending Publication Date: 2024-12-25FUJIFILM BUSINESS INNOVATION CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024049636
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-13
Filing Date
2024-03-26
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Resin films containing biodegradable resins exhibit high peel strength when stacked, making it difficult to peel them off, and increasing the particle content to reduce peel strength compromises biodegradability.

Method used

A resin film with a surface layer containing 30% or more particles by number, using cellulose structures with specific molecular weights and porous structures to distribute particles unevenly, reducing peel strength while maintaining biodegradability.

Benefits of technology

The resin film achieves excellent biodegradability and low peel strength between films, outperforming films with cellulose nanofibers or non-porous structures, and optimal particle content and diameter distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178895000001
    Figure 2024178895000001
  • Figure 2024178895000002
    Figure 2024178895000002
  • Figure 2024178895000003
    Figure 2024178895000003
Patent Text Reader

Abstract

To provide resin films that exhibit superior biodegradability while ensuring low peeling strength between the resin films.SOLUTION: A resin film includes a biodegradable resin and particles. In cross-sectional observation, the percentage of particles located in one surface layer of the film is 30 number% or more relative to all the particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin film. [Background technology]

[0002] Patent Document 1 proposes "a lactic acid-based polymer film characterized by containing, per 100 parts by weight of an acid-based polymer, 0.1 to 2 parts by weight of a lubricant and / or 0.1 to 5 parts by weight of an antiblocking agent, and 0.1 to 5 parts by weight of an antifogging agent."

[0003] Patent Document 2 proposes "a calcium carbonate filler for a resin, which comprises calcium carbonate particles having a coating layer made of a surface treatment agent formed on the surface thereof, and which is characterized by satisfying BET, particle size, and heat loss." [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-286908 [Patent Document 2] Patent Publication No. 2022-103216 Summary of the Invention [Problem to be solved by the invention]

[0005] The objective of the present invention is to provide a resin film containing a biodegradable resin and particles, which has excellent biodegradability and low peel strength between resin films, compared to a resin film in which the proportion of particles present on the surface layer of the film to all particles is less than 30% by number when observed in cross section. [Means for solving the problem]

[0006] Means for solving the above problems include the following aspects. <1> A biodegradable resin and particles are included, A resin film in which, when a cross-section is observed, the proportion of particles present on one of the film surface layers among all the particles is 30% or more by number. <2> The particles are cellulose structures containing at least one of cellulose and a cellulose derivative as a main component. <1> The resin film according to claim 1. <3> The cellulose structure is a cellulose porous structure. <2> The resin film according to claim 1. <4> The cellulose structure has an average diameter of 0.1 μm or more and 50 μm or less. <2> or <3> The resin film according to claim 1. <5> The number average molecular weight of the cellulose and the cellulose derivative is 15,000 or more and 50,000 or less. <2> ~ <4> 13. The resin film according to claim 12. <6> The cellulose derivative is cellulose acetate. <2> ~ <5> 13. The resin film according to claim 12. <7> The content of the particles relative to the biodegradable resin is 0.1% by mass or more and 10% by mass or less. <1> ~ <6> 13. The resin film according to claim 12. <8> The peel strength between the resin films is 2.5N or less. <1> ~ <7> 13. The resin film according to claim 12. Effect of the Invention

[0007] <1> or <8> According to the invention, a resin film containing particles is provided which, when observed in cross section, has excellent biodegradability and low peel strength between resin films, compared to a resin film in which the proportion of particles present on the surface layer of the film to all particles is less than 30% by number.

[0008] <2> According to the present invention, a resin film is provided which is more biodegradable and has lower peel strength between resin films than when the particles are cellulose nanofibers. <3> According to the present invention, a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with a case where the particles are made of a cellulose nonporous structure. <4> According to the present invention, a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with a case in which the cellulose structures are present with an average diameter of less than 0.1 μm or more than 50 μm. <5> According to the present invention, a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with cases where the number average molecular weight of cellulose and the cellulose derivative is less than 15,000 or more than 50,000. <6> According to the present invention, a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with the case where the cellulose derivative is cellulose acetate propionate. <7> According to the present invention, a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, compared to when the particle content relative to the biodegradable resin is less than 0.1% by mass or more than 10% by mass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described as an example. The description and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the present invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.

[0010] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of those multiple substances present in the composition.

[0011] <Resin film> The resin film according to this embodiment contains a biodegradable resin and particles, and when a cross-section is observed, the proportion of particles present on the surface layer of the film among all the particles is 30% or more by number.

[0012] The resin film according to the present embodiment has the above-mentioned structure, and has excellent biodegradability and low peel strength between resin films. The reason for this is presumed to be as follows.

[0013] In recent years, interest in biodegradable resins has been growing due to environmental awareness, as represented by the SDGs (Sustainable Development Goals). One example is the application of biodegradable resins to resin films. However, when stacking and peeling resin films, the peel strength between the resin films is high, making it difficult to peel them off. In this regard, it is known that by blending particles in a resin film and providing an uneven structure on the surface, the number of contact points between resin films can be reduced, thereby lowering the peel strength between resin films. However, commonly used particles are dispersed throughout the resin film, and in order to achieve a "reduction in the peel strength between resin films" using particles, the amount of particles must be increased, which reduces the biodegradability inherent in the biodegradable resin.

[0014] Therefore, in the resin film according to the present embodiment, the ratio of particles present in one of the film surface layers to all of the particles is set to 30% or more by number when the cross section is observed, and the particles that impart unevenness to the surface are unevenly distributed in one of the surface layers. This makes it possible to reduce the content of particles in the entire resin film while imparting surface unevenness by the particles and reducing the peel strength between the resin films, and therefore suppresses the decrease in the biodegradability of the biodegradable resin.

[0015] From the above, it is presumed that the resin film according to this embodiment has excellent biodegradability and low peel strength between resin films.

[0016] Here, examples of methods for making particles present on one of the film surface layers include a method of using a porous structure (particularly a cellulose porous structure) as particles, a method of adding particles to the surface after film formation and pressing to embed them, and a method of attaching particles to the surface when winding up the film.

[0017] The resin film according to this embodiment will be described in detail below.

[0018] (biodegradable resin) A biodegradable resin is a resin that is decomposed into water and carbon dioxide by microorganisms. Specifically, although there is no quantitative definition of the period or decomposition rate of a biodegradable resin, for the present embodiment, a resin that has a biodegradation rate of 5% or more under aerobic conditions in 28 days according to a method conforming to ISO 14855-1:2012 is defined as a biodegradable resin.

[0019] Examples of biodegradable resins include polyester resins, natural polymers, and polyvinyl alcohol.

[0020] Examples of the polyester resin include an aliphatic polyester resin and an aliphatic aromatic polyester resin. Examples of aliphatic polyester resins include polyhydroxyalkanoates such as polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoates (PHA), polycaprolactone, polybutylene succinate (PBS), polybutylene succinate / adipate (PBSA), and polyethylene succinate (PBA). Examples of the aliphatic aromatic polyester resin include polybutylene adipate / terephthalate copolymer resin (PBAT), polytetramethylene adipate / terephthalate copolymer resin, and the like.

[0021] Examples of natural polymers include starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soy protein, collagen, and keratin.

[0022] The biodegradable resin also includes cellulose derivatives (cellulose acylate, cellulose ether, hydroxyalkyl cellulose, carboxymethyl cellulose). Examples of cellulose acylate include cellulose acetate (cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).

[0023] Among these biodegradable resins, from the viewpoint of environmental compatibility, at least one selected from the group consisting of polylactic acid, polybutylene succinate, polybutylene succinate adipate, poly(3-hydroxybutyrate-co-3-hydroxypentanoate), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate), cellulose acetate, and cellulose acetate propionate is preferred, and a resin that corresponds to both a biomass resin and a biodegradable resin (particularly polylactic acid) is particularly preferred.

[0024] These biodegradable resins may be used alone or in combination of two or more kinds.

[0025] The content of the biodegradable resin in the resin composition is preferably 50% by mass or more and 99.9% by mass or less, and more preferably 90% by mass or more and 99.9% by mass or less.

[0026] (particle) Examples of the particles include cellulose structures, silica structures, acrylic structures, nylon structures, and polyolefin structures. Among these, the cellulose structure is preferable from the viewpoint of improving biodegradability. The cellulose structure is, for example, a powder containing at least one of cellulose and a cellulose derivative as a main component. By incorporating a highly biodegradable cellulose structure and a biodegradable resin into a resin film, the biodegradation rate of the entire resin film is accelerated. It is believed that the biodegradation of the cellulose structure occurs first, and decomposition enzymes and microorganisms are concentrated in the entire biodegradable resin, which accelerates the biodegradation rate of the biodegradable resin.

[0027] (Cellulose structure) The cellulose structure contains at least one of cellulose and a cellulose derivative as a main component. Here, "containing at least one of cellulose and a cellulose derivative as the main component" means that the total content of cellulose and the cellulose derivative relative to the cellulose structure is 90% by mass or more, preferably 95% by mass or more, 98% by mass or more, or 100% by mass.

[0028] Cellulose is a high molecular weight material consisting of many β-glucose molecules polymerized in a linear chain via glycosidic bonds. It is a molecular compound. On the other hand, examples of the cellulose derivatives include cellulose acylate, cellulose ether, hydroxyalkyl cellulose, and carboxymethyl cellulose. Among these, cellulose acylate is preferred as the cellulose derivative from the viewpoint of high biodegradability.

[0029] Cellulose acylate is a cellulose derivative in which at least a part of the hydroxyl groups in cellulose is replaced by an acyl group (acylation). An acyl group is a -CO-R AC (R AC represents a hydrogen atom or a hydrocarbon group.

[0030] Cellulose acylate is, for example, a cellulose derivative represented by the following general formula (CA).

[0031] [ka]

[0032] In the general formula (CA), A 1 , A 2 and A 3 Each independently represents a hydrogen atom or an acyl group, and n represents an integer of 2 or more. 1 , n A 2 and n A's 3 At least some of the n A's in the molecule represent acyl groups. 1 may be all the same, some may be the same, or different from each other. 2 and n A 3 may be entirely the same, partially the same, or different from each other.

[0033] A 1 , A 2 and A 3 The acyl group represented by the formula (I) may have a hydrocarbon group that is linear, branched, or cyclic, but is preferably linear or branched, and more preferably linear.

[0034] A 1 , A 2 and A 3 The acyl group represented by the formula (I) may have a hydrocarbon group which is either a saturated hydrocarbon group or an unsaturated hydrocarbon group, but is more preferably a saturated hydrocarbon group.

[0035] A 1 , A 2 and A 3 The acyl group represented by the formula (I) is preferably an acyl group having a carbon number of 1 to 6. That is, the cellulose acylate is preferably an acyl group having a carbon number of 1 to 6.

[0036] A 1 , A 2 and A 3 The acyl group represented by may be a group in which a hydrogen atom in the acyl group is substituted with a halogen atom (for example, a fluorine atom, a bromine atom, an iodine atom), an oxygen atom, a nitrogen atom or the like, but is preferably unsubstituted.

[0037] A 1 , A 2 and A 3 Examples of the acyl group represented by include a formyl group, an acetyl group, a propionyl group, a butyryl group (butanoyl group), a propenoyl group, a hexanoyl group, etc. Among these, from the viewpoint of improving the biodegradation rate of the resin particles, the acyl group is more preferably an acyl group having 2 to 4 carbon atoms, and even more preferably an acyl group having 2 or 3 carbon atoms.

[0038] Examples of the cellulose acylate include cellulose acetate (cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).

[0039] Of the cellulose acylates, cellulose acetate is preferred from the viewpoint of high biodegradability.

[0040] From the viewpoint of biodegradability, the degree of substitution of cellulose acylate is preferably from 1.7 to 2.9, more preferably from 1.9 to 2.6, further preferably from 2.0 to 2.5, particularly preferably from 2.1 to 2.4.

[0041] The degree of substitution of cellulose acylate is an index showing the degree to which hydroxyl groups of cellulose are substituted with acyl groups. In other words, the degree of substitution is an index showing the degree of acylation of cellulose acylate. Specifically, the degree of substitution means the intramolecular average number of substitutions in which three hydroxyl groups in the D-glucopyranose unit of cellulose acylate are substituted with acyl groups. The degree of substitution is 1 The ratio is calculated from the integral ratio of the peaks of hydrogen derived from cellulose and hydrogen derived from acyl groups using H-NMR (JMN-ECA / JEOL RESONANCE).

[0042] These cellulose derivatives may be used alone or in combination.

[0043] -Number average molecular weight of cellulose and cellulose derivatives- The number average molecular weight of cellulose and cellulose derivatives is preferably 10,000 or more and 85,000 or less, and more preferably 15,000 or more and 50,000 or less. When the number average molecular weight of the cellulose and cellulose derivative is 15,000 or more, the cellulose structure is prevented from being finely pulverized before being kneaded with the resin, which results in the prevention of secondary aggregation after pulverization, the formation of nearly uniform surface irregularities, and the reduction of the peel strength between resin films. When the number average molecular weight of the cellulose and cellulose derivatives is 50,000 or less, the decrease in biodegradability is suppressed.

[0044] The number average molecular weight of cellulose and cellulose derivatives is measured by gel permeation chromatography (differential refractometer Optilab T-rEX / Wyatt Technology, multi-angle light scattering detector DAWN HELEOS II / Wyatt Technology, columns TSKgel α-M, α-3000 each / Tosoh) using dimethylacetamide (with 0.1 M lithium chloride added) as a solvent.

[0045] The cellulosic structure may include other components. Examples of other components include plasticizers, flame retardants, compatibilizers, release agents, light resistance agents, weather resistance agents, colorants, pigments, modifiers, anti-drip agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fibers, carbon fibers, talc, clay, mica, glass flakes, milled glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc; etc.), and reactive trapping agents (for example, epoxy compounds, acid anhydride compounds, carbodiimides, etc.). The content of each of the other components is preferably 0% by mass or more and 5% by mass or less based on the total amount of the cellulose structure, where "0% by mass" means that no other components are included.

[0046] (Characteristics of cellulose structures) -Porous structure- The cellulosic structure may be a porous or non-porous structure. However, when a cellulose porous structure is used, the contact area with the biodegradable resin increases, and biodegradability is likely to improve. In addition, since the cellulose porous structure has voids inside, it has a lower specific gravity than the resin, and after kneading with the resin to obtain a resin composition, in the process of producing a resin film, it is likely to be unevenly distributed on one surface of the resin film due to the difference in specific gravity with the resin. Therefore, by applying the cellulose porous structure, it becomes easy to realize a configuration in which "when the cross section is observed, the proportion of particles present on one surface layer of the film among all particles is 30% or more by number." In addition, the cellulose porous structure has a large specific surface area, and therefore exhibits low surface energy inherent to cellulose and cellulose derivatives, thereby further exhibiting hydrophobicity and low friction. As a result, even with a small amount of the cellulose porous structure, the peel strength between the resin films can be easily reduced, and biodegradability can be easily improved.

[0047] -Specific surface area- The specific surface area of ​​the cellulose structure is 1 m 2 / g or more, more preferably 10m 2 / g or more, more preferably 20m 2 / g or more. The specific surface area of ​​the cellulose structure is 1 m 2 When the surface roughness is 1 / g or more, the low surface energy derived from cellulose and cellulose derivatives is exerted, and hydrophobicity and low friction are further exhibited, which makes it easier to reduce the peel strength between resin films. However, from the viewpoint of preventing re-aggregation in the resin, the specific surface area of ​​the cellulose structure is, for example, 150 m 2 / g or less.

[0048] The specific surface area of ​​the cellulose structure is the BET specific surface area, and is a value measured by automatic measurement using a multipoint method with a specific surface area / pore distribution measuring device (BELSORP MAXII, MicrotrackBell). The measurement temperature is 77K, and nitrogen gas is used as the adsorption gas. However, before the measurement, the sample (i.e., the cellulose structure) is subjected to a pretreatment such as vacuum drying at 100° C. for 24 hours to remove water adsorbed in the pores of the sample.

[0049] -Porosity- The porosity of the cellulose structure is preferably 10% or more and 50% or less, and more preferably 20% or more and 50% or less. If the porosity of the cellulose structure is 10% or more, it is likely to be unevenly distributed on one surface of the resin film due to the difference in specific gravity with the resin during the process of kneading the cellulose structure with the resin to obtain a resin composition and producing a resin film. Therefore, it is easy to realize a configuration in which "when observing the cross section, the proportion of particles present on one surface layer of the film among all particles is 30% or more by number." As a result, the peel strength between the resin films is likely to be reduced. When the porosity of the cellulose structure is 50% or less, the cellulose structure is prevented from being finely disintegrated before being kneaded with the resin, which results in suppressing secondary aggregation after disintegration, realizing the provision of nearly uniform surface irregularities to the resin film surface, and facilitating the reduction of the peel strength between the resin films.

[0050] The porosity of the cellulose structure is measured as follows. The cellulose structure is observed at a magnification of 25,000 times using a scanning electron microscope (SEM) to obtain an SEM image. The SEM image is imported into the image processing software "ImageJ" and binarized to determine the area of ​​the entire cellulose structure and the area of ​​the voids. The ratio of the voids in the cellulose structure to the area of ​​the entire cellulose structure is then calculated to determine the porosity of the cellulose structure. This operation is carried out 10 times and the average value is calculated.

[0051] -specific gravity- The specific gravity of the cellulose structure is 0.5 g / cm 3 More than 1.15g / cm 3 Less than 0.6 g / cm is preferred. 3 More than 1g / cm 3 Less than 0.7 g / cm is more preferable. 3 More than 0.9g / cm 3 The following is even more preferred: When the specific gravity of the cellulose structure is within the above range, the cellulose structure is likely to be unevenly distributed on one surface of the resin film due to the difference in specific gravity with the resin during the process of kneading the cellulose structure with the resin, obtaining a resin composition, and producing a resin film. Therefore, it is easy to realize a configuration in which "when observing a cross section, the proportion of particles present on one surface layer of the film among all particles is 30% or more by number." As a result, the peel strength between the resin films is likely to be reduced.

[0052] The specific gravity of the cellulose structure was measured as follows. 30 g of the structure was used as a sample, and measurements were performed by the immersion method using an automatic specific gravity meter (DSG-1, manufactured by Toyo Seiki Seisakusho Co., Ltd.), except that the measurement liquid was changed from water to ethanol.

[0053] (Method of producing cellulose structure) The cellulose structure according to this embodiment can be obtained, for example, by the following method. (1) A cellulose derivative is added to a good solvent for the cellulose derivative, and then heated to obtain a solution A in which the cellulose derivative is dissolved in the good solvent. (2) A poor solvent for the cellulose derivative is added to solution A to obtain solution B. (3) Solution B is rapidly cooled, and a gel-like substance of the cellulose derivative is produced by phase separation. (4) After the gel-like substance is washed, it is dried to obtain a cellulose porous structure whose main component is a cellulose derivative. (5) The obtained cellulose porous structure may be crushed and sieved to remove coarse particles and aggregates, if necessary. The crushing method is not particularly limited, but may be performed using a dry grinding device such as a jet mill, a vibration mill, a ball mill, or a pin mill. The sieving method may be performed using a known device such as a vibration sieve or an air sieving machine.

[0054] Here, the gel-like substance is saponified (that is, the cellulose derivative is saponified), and depending on the degree of saponification, a cellulose porous structure mainly composed of cellulose or cellulose and a cellulose derivative is obtained.

[0055] To obtain a non-porous cellulose structure, there are methods such as obtaining cellulose particles by a suspension emulsification method and crushing a raw material of cellulose acetate (DAC).

[0056] (Other ingredients) The resin film according to this embodiment may contain other components. Examples of other components include plasticizers, flame retardants, compatibilizers, release agents, light resistance agents, weather resistance agents, colorants, pigments, modifiers, anti-drip agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fibers, carbon fibers, talc, clay, mica, glass flakes, milled glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc; etc.), and reactive trapping agents (for example, epoxy compounds, acid anhydride compounds, carbodiimides, etc.). The content of each of the other components is preferably 0% by mass or more and 5% by mass or less based on the total amount of the resin film, where "0% by mass" means that no other components are included.

[0057] (Particle content) The content of the particles (particularly the cellulose structure) is preferably from 0.1 to 20% by mass, more preferably from 0.5 to 10% by mass, and even more preferably from 1 to 5% by mass, based on the biodegradable resin. When the content of the particles (particularly the cellulose structure) is within the above range, it becomes easy to obtain a resin film that is sufficiently biodegradable and has reduced peel strength between resin films.

[0058] (Characteristics of resin film) -The ratio of particles present on the surface of one film to the total number of particles- In the resin film according to this embodiment, when a cross-section of the resin film is observed, the proportion of particles present on one of the film surface layers to all particles is 30% by number or more, preferably 35% by number or more, and more preferably 40% by number or more. However, from the viewpoint of maintaining surface smoothness, the proportion of particles is preferably 70% by number or less. By making the ratio of particles 30% by number or more, a resin film having high biodegradability and reduced peel strength between resin films can be obtained.

[0059] -Average diameter of cellulose structures in resin film- The cellulose structure preferably has an average diameter of 0.1 μm or more and 50 μm or less, more preferably 1 μm or more and 20 μm or less, and even more preferably 1 μm or more and 10 μm or less. When the cellulose structure is present with an average diameter of 0.01 μm or more, the contact points between the resin films due to surface irregularities are sufficiently reduced, making it easier for the strength between the resin films to decrease. When the cellulose structure has an average diameter of 50 μm or less, fine surface irregularities are formed, which tends to reduce the peel strength between resin films.

[0060] The proportion of particles present in one of the film surface layers and the average diameter of the cellulose structures present in the resin film are measured as follows. A sample piece having a cut surface is obtained by cutting the resin film to be measured along the thickness direction. The cut surface of the sample piece is observed with a scanning electron microscope (SEM) at a magnification of 1000 times to obtain an SEM image. The SEM image is an image in which the entire cross section of the resin film can be observed. The SEM image is imported into the image processing software "ImageJ" and the number of particles present in the entire cross section of the resin film is calculated. In addition, the surface layer region 10 μm deep from one surface of the resin film is regarded as the surface layer of the resin film, and the number of particles present in this surface layer region is calculated. Note that particles that overlap the boundary of this region are counted as particles present in this region. The ratio (number %) of particles present in the surface layer region to the total number of particles present in the entire cross section of the resin film is then calculated, and this operation is repeated five times to calculate the average particle ratio. In addition, the SEM image is imported into the image processing software "ImageJ", and the circle equivalent diameter is calculated from the area of ​​the cellulose porous structures dispersed in the resin film. The average circle equivalent diameter of the 20 cellulose porous structures is then calculated, and this is taken as the average diameter of the cellulose structures present in the resin film.

[0061] When observing the cross section of the resin film, the proportion of particles present on the other surface layer of the film to all particles is not particularly limited, but is preferably less than 30% by number, less than 20% by number, or less than 10% by number.

[0062] (biodegradation rate) In the resin film according to this embodiment, the biodegradability measured by a method conforming to ISO 14855-1:2012 JIS 14855-1 is preferably 30% or more, more preferably 50% or more, and even more preferably 70% or more, over 28 days. When the biodegradability is within the above range, the resin film has sufficiently high biodegradability.

[0063] (Peel strength between resin films) The peel strength between the resin films according to this embodiment is preferably 2.5 N or less, more preferably 2 N or less, and even more preferably 1.5 N or less. When the peel strength between the resin films is within the above range, the resin films have a sufficiently reduced peel strength between the resin films.

[0064] The biodegradability and peel strength between resin films are values ​​measured by the methods described in the "Examples" section below.

[0065] (Method of manufacturing resin film) Examples of the method for producing the resin composition according to the present embodiment include a method of mixing particles and a biodegradable resin and melt-kneading the mixture. The melt-kneading means is not particularly limited, and examples thereof include a twin-screw extruder, a Henschel mixer, a Banbury mixer, a single-screw extruder, a multi-screw extruder, and a co-kneader. Here, when a cellulose structure (particularly a cellulose porous structure) is used as the particles, by controlling the kneading conditions, a resin composition containing a biodegradable resin and a disintegrated material (i.e., a cellulose structure) in which the raw cellulose structure is disintegrated by kneading with the biodegradable resin can be obtained. The resin composition is then formed into a film using a film processing device to obtain a resin film.

[0066] Here, the starting cellulose structure to be used is preferably one having an average diameter of 1 μm or more and 500 μm or less (preferably 5 μm or more and 355 μm or less, more preferably 10 μm or more and 100 μm or less). When the average diameter of the raw cellulose structure is 1 μm or more, when the raw cellulose structure is kneaded with a resin, the cellulose porous structure collapses, and the contact points between resin films due to surface unevenness are sufficiently reduced, making it easier to reduce the peel strength between resin films. When the average diameter of the raw cellulose structure is 500 μm or less, the cellulose porous structure is prevented from being finely disintegrated before being kneaded with the resin, which results in suppressing secondary aggregation after disintegration, realizing the imparting of nearly uniform surface irregularities to the resin film surface, and facilitating the reduction of the peel strength between the resin films.

[0067] The average diameter of the raw cellulose structure was measured as follows. The cellulose porous structure is observed at a magnification of 250 times using a scanning electron microscope (SEM) to obtain a threshold SEM image. The SEM image is imported into the image processing software "ImageJ" and the circle equivalent diameter is calculated from the area of ​​the cellulose porous structure. The average circle equivalent diameter of 20 cellulose porous structures is then calculated and used as the average diameter.

[0068] The raw cellulose structure has the same configuration as the above-mentioned cellulose structure except for the above-mentioned average diameter, and therefore the description thereof will be omitted.

[0069] Applications of the resin film according to this embodiment include packaging films, lamination films, light diffusion films, electrode films, and decorative films. EXAMPLES

[0070] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.

[0071] <Preparation of cellulose structures> (Cellulose Structure CS(1)) In a container, 5 parts by mass of cellulose acetate DAC(1) was added to 20 parts by mass of dimethylformamide to form solution A, which was stirred at 90°C for 1 hour. After dissolving cellulose acetate in dimethylformamide in solution A, 25 parts by mass of hexanol was slowly added to solution A while stirring, and the resulting solution B was stirred for 1 hour. Then, solution B was immersed in ice water together with the container to rapidly cool, and a gel product of a cellulose structure was obtained by phase separation. The resulting gel product was washed with 200 parts by mass of ethanol and vacuum dried at 50°C for 24 hours to obtain a cellulose structure. The structure was then crushed in a mill mixer and sieved through a 106 μm sieve to obtain a finely pulverized cellulose structure.

[0072] (Cellulose Structure CS(2)) A cellulose structure CS(2) was obtained in the same manner as the cellulose structure CS(1), except that the mesh size of the sieve was 38 μm.

[0073] (Cellulose Structure CS(3)) A cellulose structure CS(3) was obtained in the same manner as for the cellulose structure CS(1), except that the amount of cellulose acetate was 7.5 parts by mass.

[0074] (Cellulose Structure CS(4)) A cellulose structure CS(4) was obtained in the same manner as for the cellulose structure CS(1), except that the amount of cellulose acetate was 3.5 parts by mass.

[0075] (Cellulose Structure CS(5)) A cellulose structure CS(5) was obtained in the same manner as for the cellulose structure CS(1), except that the cellulose acetate DAC(1) was changed to DAC(2).

[0076] (Cellulose Structure CS(6)) A cellulose structure CS(6) was obtained in the same manner as for the cellulose structure CS(1), except that the cellulose acetate DAC(1) was changed to DAC(3).

[0077] (Cellulose Structure CS(7)) A cellulose structure CS(2) was obtained in the same manner as for the cellulose structure CS(1), except that the cellulose acetate DAC(1) was changed to DAC(4).

[0078] (Cellulose Structure CS(8)) A cellulose structure CS(8) was obtained in the same manner as the cellulose structure CS(1), except that cellulose acetate was changed to triacetyl cellulose.

[0079] (Cellulose Structure CS(9)) A cellulose structure CS(9) was obtained in the same manner as the cellulose structure CS(1), except that cellulose acetate was changed to cellulose acetate propionate.

[0080] (Cellulose Structure CS(10)) A cellulose structure CS(10) was obtained in the same manner as the cellulose structure CS(1), except that cellulose acetate was changed to cellulose acetate butyrate.

[0081] (Cellulose Structure CS(11)) The cellulose structure CS(11) was obtained in the same manner as the cellulose structure CS(1), except that the gel product was subjected to alkaline saponification before washing with ethanol.

[0082] (Cellulose Structure CS(12)) A cellulose structure CS(12) was obtained in the same manner as the cellulose structure CS(1), except that the mesh size of the sieve was 500 μm.

[0083] (Cellulose Structure CS(13)) A cellulose structure CS(13) was obtained in the same manner as the cellulose structure CS(1), except that sieving after crushing was not performed.

[0084] (Cellulose Structure CS(14)) A cellulose structure CS(14) was obtained in the same manner as for the cellulose structure CS(1), except that the amount of dimethylformamide was changed to 120 parts by mass and the amount of hexanol was changed to 370 parts by mass.

[0085] (Cellulose Structure CS(15)) A cellulose structure CS(15) was obtained in the same manner as the cellulose structure CS(1), except that the cellulose acetate DAC(1) was changed to DAC(5).

[0086] (Cellulose Structure CS(C1)) Cellulose acetate DAC (1) was crushed in a mill mixer and then sieved through a 106 μm sieve to obtain a cellulose structure (C1).

[0087] (Cellulose Structure CS(C2)) 130 parts by mass of cellulose acetate DAC(1) was dissolved in 870 parts by mass of ethyl acetate. This was added to a dispersion of 50 parts by mass of calcium carbonate dispersed in 500 parts by mass of pure water, and stirred for 3 hours. This was added to a dispersion of 4 parts by mass of carboxymethylcellulose and 200 parts by mass of methyl ethyl ketone dispersed in 600 parts by mass of pure water, and stirred for 5 minutes with a high-speed emulsifier. 10 g of sodium hydroxide was added to this, and the mixture was stirred at 80°C for 3 hours to remove ethyl acetate and methyl ethyl ketone. 10 g of dilute hydrochloric acid was added to this, and the residue was filtered to obtain nonporous cellulose particles.

[0088] (Characteristics of cellulose structures) The following properties of the obtained cellulose structure were measured according to the methods described above. Average diameter of cellulose structures - Specific surface area of ​​cellulose structure (indicated as "BET" in the table) Porosity of cellulose structures · Specific gravity of cellulose structure

[0089] <Examples 1 to 22 and Comparative Examples 1 to 4> Each component was charged into a twin-screw extruder (Shibaura Machine Co., Ltd., TEM58SS) under the conditions of composition, cylinder temperature, and kneading torque shown in Table 1, and each component was kneaded, cooled, and cut to obtain resin pellets (corresponding to the resin composition). The resin composition was then charged into a film processing device (Labo Plastomill, film processing unit, manufactured by Toyo Seiki Seisakusho) under the conditions of the cylinder temperature and roll temperature shown in Table 1, and the resin composition was formed into a film to obtain a resin film 50 mm wide x 200 μm thick, which was then wound into a roll to obtain a tall film. The tall film was then cut into a width of 20 mm x length of 70 mm to obtain a short resin film.

[0090] <Evaluation> (Proportion of particles present on the film surface) When the cross section of the resin film was observed, the proportion of particles present on one of the film surface layers to all particles (in the table, indicated as "proportion of particles present on the film surface layer") was measured according to the method already described. In addition, when the cross section of the resin film of the example was observed, it was confirmed that the ratio of particles present on the other film surface layer to all particles was less than 10% by number.

[0091] (Dispersion diameter) The average diameter of the cellulose structures present in the resin film (represented as "dispersed diameter" in the table) was measured according to the method already described.

[0092] (biodegradation rate) The resin pellets obtained were crushed using a lab mill (Dalton, LM-05), then sieved through a 100 μm mesh, and the part that passed through was collected. The collected material was subjected to aerobic biodegradation measurement according to ISO 14855-1:2012, and the biodegradation rate after 28 days was calculated.

[0093] (Peel strength between resin films) Two of the obtained resin films were used, and a Teflon (registered trademark) sheet of 30 mm width × 30 mm length was sandwiched between the two resin films so that the area of ​​direct contact between the two resin films was 20 mm width × 40 mm length to obtain a laminated film. The laminated film was pressed at a temperature of 30°C and a pressure of 2 MPa to obtain a test film in which only the direct contact area was fused. Using the test film, a tensile test was performed at a test speed of 1 mm / min using a universal material testing machine (Strograph VG, manufactured by Toyo Seiki Seisakusho) by clamping the unfused portion of the film. The test force at the time of peeling was measured as the peel strength between the resin films.

[0094] <Materials used> The materials used will be described in detail below. -Raw materials for additives- DAC(1): Eastman Chemical Co., Ltd. "Product name CA398-3", cellulose diacetate, number average molecular weight Mn=15000 DAC(2): Daicel Corporation, "Product name L20", cellulose diacetate, number average molecular weight Mn=15000 DAC(3): Daicel Corporation, "Product name L50", cellulose diacetate, number average molecular weight Mn=50,000 DAC(4): Daicel Corporation, "Product name L70", cellulose diacetate, number average molecular weight Mn=75,000 ·DAC(5): In-house synthesized cellulose diacetate, number average molecular weight Mn=13000, TAC: Daicel Corporation, "Product name LT-35", cellulose triacetate, number average molecular weight Mn=50,000 CAP: Eastman Chemical Co., Ltd. Product name: CAP482-20 72000 CAB: Eastman Chemical Co., Ltd. "Product name CAB382-10", cellulose acetate butyrate, number average molecular weight Mn = 85,000 CNF (1): Sugino Machine Co., Ltd. "Product name: BinFIS DRY", cellulose nanofiber CNF(2): Cellulose fine powder (manufactured by Daio Paper Co., Ltd., product name ELLEX-P) CS(C3): AGC Si-Tech Co., Ltd. "Product name: Sunsphere H-51" CS(C4): Sigma-Aldrich Co., Ltd. (product name: MCM41)

[0095] -Biodegradable resin- PLA: Polylactic acid (Natureworks, Ingeo3001D) PBS: Polybutylene succinate (Bio-PBS manufactured by PTT MCC Biochem) ·PBSA: Polybutylene succinate adipate (PTT MCC Biochem Bio-PBSA) CAP: Cellulose acetate propionate (Eastman Chemical, CAP482-20)

[0096] [Table 1-1]

[0097] [Table 1-2]

[0098] From the above results, it is evident that in this Example, a resin film having excellent biodegradability and low peel strength between resin films can be obtained as compared with the Comparative Example.

[0099] The present embodiment includes the following aspects. (((1))) A biodegradable resin and particles are included, A resin film in which, when a cross-section is observed, the proportion of particles present on one of the film surface layers among all the particles is 30% or more by number. (((2))) The resin film according to (((1))), wherein the particles are cellulose structures containing at least one of cellulose and a cellulose derivative as a main component. (((3))) The resin film according to (((2))), wherein the cellulose structure is a porous cellulose structure. (((4))) The cellulose structure has an average diameter of 0.1 μm or more and 50 μm or less. The resin film according to (((2))) or (((3))) is present. (((5))) The resin film according to any one of (((2))) to (((4))), wherein the cellulose and the cellulose derivative have a number average molecular weight of 15,000 or more and 50,000 or less. (((6))) The resin film according to any one of ((2))) to (((5))), wherein the cellulose derivative is cellulose acetate. (((7))) The resin film according to any one of (((1))) to (((6))), wherein the content of the particles relative to the biodegradable resin is 0.1% by mass or more and 10% by mass or less. (((8))) The resin film according to any one of ((1))) to (((7))), wherein a peel strength between the resin films is 2.5 N or less.

[0100] The advantages of the above aspect are as follows. According to the invention related to (((1))) or (((8))), a resin film is provided which, in a cross-sectional observation of a resin film containing particles, has excellent biodegradability and low peel strength between resin films, compared to a resin film in which the proportion of particles present on the surface layer of the film to all particles is less than 30% by number.

[0101] According to the invention related to (((2))), a resin film is provided which is more biodegradable and has lower peel strength between resin films than when the particles are cellulose nanofibers. According to the invention related to (((3))), a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with a case where the particles are made of a non-porous cellulose structure. According to the invention related to (((4))), a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, compared to when the cellulose structure is present with an average diameter of less than 0.1 μm or more than 50 μm. According to the invention (((5))), a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, compared to cases where the number average molecular weight of cellulose and the cellulose derivative is less than 15,000 or more than 50,000. According to the invention related to (((6))), a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, as compared with the case where the cellulose derivative is cellulose acetate propionate. According to the invention (((7))), a resin film is provided which is excellent in biodegradability and has low peel strength between resin films, compared to when the particle content relative to the biodegradable resin is less than 0.1% by mass or more than 10% by mass.

Claims

1. A biodegradable resin and particles are included, A resin film in which, when a cross-section is observed, the proportion of the particles present on one of the film surface layers to all the particles is 30% or more by number.

2. 2. The resin film according to claim 1, wherein the particles are cellulose structures containing at least one of cellulose and a cellulose derivative as a main component.

3. The resin film according to claim 2 , wherein the cellulose structure is a porous cellulose structure.

4. 3. The resin film according to claim 2, wherein the cellulose structure has an average diameter of 0.1 μm or more and 50 μm or less.

5. 3. The resin film according to claim 2, wherein the cellulose and the cellulose derivative have a number average molecular weight of 15,000 or more and 50,000 or less.

6. 3. The resin film according to claim 2, wherein the cellulose derivative is cellulose acetate.

7. The resin film according to claim 1 , wherein the content of the particles relative to the biodegradable resin is 0.1% by mass or more and 10% by mass or less.

8. 2. The resin film according to claim 1, wherein the peel strength between the resin films is 2.5 N or less.

Citation Information

Patent Citations

  • Lactic acid-based polymer film

    JP1997286908A

  • Calcium carbonate filler for resin and resin composition containing same

    JP2022103216A